Impact of Security Threats on Investment in Nigeria - Isa Jibrin OKPE; Victor Ushahemba IJIRSHAR; Amina Shehu IBRAHIM; Samuel Igwe OGODA (CECCAR Business Review, 2024)

(untitled)
A study on the relationship between security threats and investment in Nigeria is essential for providing empirically data-driven insights into how security challenges, such as insurgency, crime and instability, influence investment decisions. This research can guide policymakers, investors and stakeholders in formulating effective strategies to mitigate risks, enhance investor confidence and promote economic growth. This study employed the vector error correction model method to examine the association between security threats and investment in Nigeria from 1986 to 2021. The analysis of the long-term perspective revealed an adverse relationship between security threats and domestic investment and between security threats and foreign direct investment in Nigeria. Additionally, the study revealed that although security threats do not substantially influence domestic investment in the short run, they exhibit a pronounced adverse impact on economic growth in the long run. Consequently, security threats significantly affect domestic investment and foreign direct investment in Nigeria in the long run. As a result, the study suggests that the Nigerian government should enhance security measures to counteract issues such as political instability, terrorism and social unrest, thereby cultivating a more conducive business environment that stimulates both domestic and foreign investment activities.